Nigel Dower, An Introduction to Global Citizenship - Crook, Seth (Journal for the study of religion, nature and culture, 2004)
Nigel Dower, An Introduction to Global Citizenship (Edinburgh: Edinburgh University Press, 2003), pp. 224. Paperback, ISBN 0-7486-1470-2, £12.99. Hardback, ISBN 0-7486-1469-9, £45.00.